Pharmacokinetics and tissue distribution of a novel PDE5 inhibitor, SK-3530, in rats - Yoo, Hye-hyun; Kim, Nam-sun; Im, Guang-jin; Kim, Dong-hyun (ACTA PHARMACOLOGICA SINICA, 2007)
Aim: To investigate the pharmacokinetic profile and tissue distribution of a novel phosphodiesterase type 5 inhibitor, 5-ethyl-2-{5-[4-(2-hydroxy-ethyl)-piperazine-1-sulfonyl]-2-propoxy-phenyl}-7-propyl-3,5-dihydro-pyrrolo(3,2-d)pyrimidin-4-one (SK-3530), in rats after administration of the C-14-labeled compound. Methods: The pharmacokinetic parameters of SK-3530 were measured based on the total radioactivity and parent SK-3530 concentration in rat plasma after intravenous and oral administration. The tissue distribution of total radioactivity after a single oral administration of [C-14]SK-3530 at a dose of 40 mg/kg was assayed. The plasma protein binding rates of SK-3530 were assessed by in vitro and ex vivo assay. Results: The total radioactivity profiles showed linear pharmacokinetics. The maximum plasma concentration and area under the curve of the parent SK3530 were 10%-20% compared to those of the total radioactivity. After the oral administration of [C-14]SK-3530, the radioactivity was widely distributed in all tissues, and the tissue/plasma ratio of the radioactivity 1 h after administration was calculated as 0.5-2.6 with the exception of excretory organs. Arelatively high penetration was shown in the adrenal glands, liver, and lung. In vitro and ex vivo plasma protein binding assay by ultrafiltration showed a considerably high binding rate of more than 97%. Conclusion: SK-3530 was relatively well absorbed in the gastrointestinal tract and showed linear pharmacokinetics over the investigated dose range. SK-3530 had low oral bioavailability due to a high, first-pass metabolism.
Keywords: PHOSPHODIESTERASE TYPE 5; ERECTILE DYSFUNCTION; SILDENAFIL; HEADACHE; BLOOD; DOG